Lime Requirements of Highly Weathered Malaysian Soils - Jusop, Shamsuddin (1989)
methods of determining lime requirements for weathered Malaysian soils were tested. Eight soil series were selected, of which 5 were Ultisols and 3 were Oxisols. The methods tested were incubation with GML (regarded as reference methods), titration with Ca(OH)2 (3 methods) and a method based on exchangeable Al. The result showed that the titration method of Dunn (1943) was well correlated with the incubation method. Determination of lime requirement based on exchangeable Al gave a good estimate of lime requirements fOr Ultisol, but not for Oxisol. The responses of soils to GML over time and rate of application are also discussed.